HAMILTON-JACOBI TREATMENT OF LAGRANGIANS WITHIN FRACTIONAL CAPUTO DERIVATIVES - Ali M Qudah (European Scientific Journal, ESJ, 2013)
In this work, the Hamilton-Jacobi formulation of fractional Caputo Lagrangians of linear velocities is investigated. The fractional Hamilton-Jacobi equations of motion for several potential systems are derived. Under certain conditions on the potential, it is shown that the action integral is independent on the fractional Caputo derivatives.